Proactive and reactive styles of Palestinian presidents leadership in times of crisis / Mohammed Fadel Arandas ... [et al.] - Arandas, Mohammed Fadel; Idid, Syed Arabi; Ling, Loh Yoke; Chiang, Loh Yu (Universiti Teknologi MARA, 2022)
Crises are unavoidable which makes response an imperative matter. Thus, the proactive style becomes an indispensable part of the readiness and preparedness in any potential crisis and can help prevent it. Besides, the reactive style is still important to deal effectively with a crisis especially regarding its recovery. Proactive and reactive styles were needed by Palestinian Presidents due to the occurrence of various crises faced by them. This study examines both proactive and reactive styles used by the Palestinian Presidents leadership during crisis. Besides, it examines how the Palestinian Presidents used these styles to deal with different crises at different times. This study used content analysis on the news stories from the New Straits Times. A total of 313 stories from1996 to 2016 pertaining to proactive and reactive styles used by Palestinian Presidents were found. The stories that included reactive style figured 67.7%, while the stories that included proactive style totaled 32.3%. For President Arafat, a total of 63% of the stories included reactive style compared to 37% of the stories that included proactive style. For President Abbas, a total of 78.4% of the stories contained reactive style compared to 21.6% that contained proactive style. Proactive style has been used only in political crises, while reactive style has been used in all crises. Providing various scenarios in dealing with crises allows other organizations and individuals to be initiative in dealing with any similar future crises. This study serves as a guideline for choosing proper prospective measures and responses to crises.